Finansowanie zadań oświatowych przez samorządy gminne - Rechul, Halina (Financing Educational Tasks By Local Governments, 2009)
The article presents an analysis of financing the educational tasks by local governments for whom running public kindergartens, primary schools and middle schools have become a direct responsibility. The results of the analysis show that resources coming from the national budget in form of general educational subsidies as well as budget grants do not cover actual expenses on educational tasks in the communes. Therefore, local authorities bear additional expenses on education also using their own revenue
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 271-176